Conceptualization of organizational indifference using cognitive mapping - Mohammad Golmohammadi, Gholamreza Malekzadeh, (Opción, 2019)
The current article aims to investigate the employees’ indifference toward organizations, identifying the factors causing this phenomenon and its consequences for the management of organizations. Cognitive mapping is a qualitative research method that allows graphical description of organizational issues and problems in this research. As a result, by analyzing data sources, the management solutions of employees’ indifference are divided into four structural, managerial, individual and occupational categories. As a conclusion, the identification of this phenomenon and its aspects can help organizations prevent it to happen